RECORDS PRESERVING AND CONSERVATIVE ENDANGERED SCRIPTS VIA ELECTRONIC ARCHIVE OF NORTH EAST REGION OF INDIA: WITH SPECIAL REFERENCE TO ASSAM. (International Journal of Food and Nutritional Sciences, 2022)
Present study examines the preservation and conservation of manuscripts in Assam, India, with afocus on linguistic diversity, temporal distribution, and script variations. The objectives includeanalyzing the linguistic diversity of manuscripts, investigating their temporal distribution, andexamining script variations to understand the region's cultural heritage.